Status of observance of structural standards in rehabilitation centers and nursing homes - Malihe Foruoghi; Mahrokh Keshvari; Saeeid Sadeghi; Parvaneh Abazari (Wolters Kluwer Medknow Publications, 2018)
Introduction: The purpose of this study was to determine the status of observance of structural standards in rehabilitation centers and nursing homes. Materials and Methods: This cross-sectional descriptive study was carried out on 12 centers of the nursing homes of Isfahan city during 2016-2017. The tool was a check. To complete the checklist, the direct observation of the environment and the review of existing documents were used. Data were analyzed by descriptive statistics and frequency distribution. Results: The findings of this study shows that of 11 standards ofworkforce standards regarding to health expert presence, nurse presence, therapist and extracurricular instructor presence, have been observed innone of the centers, and the presence of social worker/psychologist in 50% of the centers. Of the 21 standards relating to the physical environment, eight standards have not been met in any of the centers. Of the 25 standards relating to the general conditions of building, 4 standards have not been met in any of the centers. Of the 10 standard relating to the equipment and supplies which are needed, 3 were not observed in any of the centers. Of the 10 standards relating to the required services, except one, standards have been met in all centers. Of the 10 standards relating to the general provisions, 7 are met in all centers of both types. Conclusion: According to the findings, a significant percentage of standards have not been met in any of the aging centers or just met in some of these centers. It is hoped that the results of this study will enable authorities to promote standardization of nursing homes and rehabilitation centers.